Livelihood and income generation from the woodcarving trade in the Cape Town area of the Western Cape Province, South Africa - Mikolo Yobo, Christian (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScFor) (Forest and Wood Science)--University of Stellenbosch, 2007.